PENGARUH SEKTOR PENDIDIKAN FORMAL TERHADAP TINGKAT PENYERAPAN TENAGA KERJA DI KECAMATAN BARABAI : Studi Kasus Pendidikan Tingkat SLTA/ Sederajat dan S.1 - Haris Irawan (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2017)
Abstract, The research objective is to: determine the effect of formal education sector to the level of employment in the District Barabai Hulu Sungai Tengah. The main data used in this study are: (1) Data on the number of high school graduate level education and S1 from the year 2007 to 2012 in the District Barabai Hulu Sungai Tengah, and (2) Data employment in the District Barabai by education level of the year 2007-2012. The results showed: (1) Based on t test known variable formal education sector (high school / equivalent and S.1) (X) a significant effect on employment in the District Barabai. This is evidenced from the results of the test at significance level of 5% t is greater than t table (t-test = 6.767> t-table = 2.132), and (2) The coefficient of determination of 0.919, which means that the independent variables: the formal education sector ( X) have accounted for 91.9% of variance on the dependent variable: absorption of labor in the District Barabai Hulu Sungai Tengah (Y), while the remaining 8.1% is given by other variables that are not included in this study.